PENDIDIKAN ISLAM BERBASIS KELUARGA DALAM PERSPEKTIF ABDULLAH NASHIH ULWAN DI ERA MILENIAL - Evi Fatimatur Rusydiyah; Nasarudin Nasarudin (Institut Keislaman Abdullah Faqih (INKAFA) Gresik, 2020)
Abstract: The most important and strategic educational institution is the family. This is because the challenge of Education today is facing the millennial era. This era is marked by disruptive, post truth, and hedonism. Families as filters in facing the challenges of the era. This paper aims to analyze Abdullah Nashih Ulwan's views on family-based Islamic education in the millennial era. The study in this paper applies the descriptive analysis method and the type of library research that uses library sources to obtain data or information. The results of this study are Abdullah Nashih Ulwan's views on family-based Islamic education. According to Abdullah Nashih Ulwa's view, the urgency function of the family in shaping the personality of the child as one of the educational institutions can be through the material provided to the child, including religious, physical, moral, intellectual, sexual, and psychological education material, while the right method is the method exemplary, advice, customary habits, attention and supervision as well as punishment. Through material and methods applied in the family environment, it can deliver the righteous and pious children as expected by religion, society and parents.Keyword: Islamic education, Family, Millennial Era